Enhanced reservoir flood prevention by using leveraging sensor technology - Saida Angotu; Rani Sowmya Jorrigala; Poorna Chandra Laxman Guttala; Swetha G.; Verma Vikas (MATEC Web of Conferences, 2024)
The project focuses on the development of an intelligent flood management system utilizing Arduino-based hardware components to estimate reservoir inflow. By integrating data from rainfall and soil moisture sensors, coupled with potential inputs from upstream reservoirs, the system aims to dynamically control reservoir gates. The primary goal is to prevent flooding in the basin by implementing controlled water releases. The Arduino microcontroller processes real-time sensor data, triggering the activation of a servo motor to simulate the opening and closing of reservoir gates. The system's efficacy is enhanced by considering diverse soil types and land uses within the watershed. This automated approach not only addresses the challenges posed by uncontrolled urbanization and legal constraints but also provides a cost-effective and efficient solution for flood prevention. The project's potential impact extends to various sectors, including agriculture, industries, and residential areas, ensuring the safety of communities and safeguarding against the adverse effects of floods.